Low level phosphorus supply affecting nodulation, N2 fixation and growth of cowpea (Vigna unguiculata L. Walp) - Wan Othman, W. M.; Lie, T. A.; Mannetje, L. 't; Wassink, G. Y. (Springer, 1991)
The interactive effect of low P supply (0, 10, 20 and 40 μM) and plant age on nodule number, mass and functioning (ureide analysis technique), vegetative growth and pod production were investigated in glasshouse-grown nodulated cowpea (Vigna unguiculata L.cv. Kausband) in sand culture. Compared with 40 μM P, P stress (0 μM P) or very low (10 μM P) supply markedly impaired nodulation, allantoin and amino-N concentrations and weight of N solutes in xylem exudates. Consequently, P stress reduced top growth and pod yields by 48 and 90%, respectively. N solutes in xylem exudates and total plant N assayed by Kjeldahl technique (as estimates of N2 fixation) responded similarly to P supply. However, the relative ureide index [(ureide-N/ureide N+amino-N)×100] remained constant (99%), irrespective of P supply, indicating the plants' complete dependency on symbiosis for growth, without implying that growth was markedly increased by N2 fixation. Although P concentrations in plant tops, roots and nodules increased with P supply, N concentrations in these plant tissues were unaffected by P supply. The concentrations of N and P in the nodules were 2–2 1/2 times higher than in plant tops. P application interacted strongly with plant age, with the largest P effect evidently achieved at the early podding stage. The significance and implications of these results are discussed.